Improving SME logistics performance through benchmarking. Issue 7 (3rd October 2016) - Taschner, Andreas
Abstract : Purpose: The purpose of this paper is to discuss the applicability of current benchmarking proposals for small and medium-sized enterprises (SMEs) and to suggest a condensed process for logistics benchmarking in SMEs. Design/methodology/approach: The paper starts by outlining why the logistics function is of increasing importance for SMEs. It discusses the benefit of logistics benchmarking and typical SME restrictions in benchmarking. Available approaches to benchmarking are discussed and their weaknesses when applied to SME logistics benchmarking are analyzed. The paper develops a new benchmarking process framework for SME logistics benchmarking and reports findings of a case application in three German SMEs. Findings: The paper suggests a conceptual framework for logistics benchmarking in SMEs. The framework was tested in three German case companies. Results suggest that the suggested process together with the employed benchmarking tools and templates provide valuable support for SMEs in a logistics benchmarking project. Research limitations/implications: The conceptual framework developed has been tested in selected case companies only. Possible adaptations to specific industry needs or cultural differences need to be integrated. Practical implications: The process framework developed provides practical guidance for SMEs that want to embark on a logistics benchmarking exercise. Originality/value: The paper outlines weaknesses of current SME benchmarking approaches and provides practical support by outlining an adapted process together with specific implementation tools.